Management Of Non-Performing Assets (Npa) In Banks – With Special Reference To Union Bank Of India - Saha, Monti; Zaman, Aminuz; Basumatary, Priyo (The journal of contemporary issues in business and government, 2021)
The term non-performing asset can be defined as those advances or loans which are in arrears or in defaults. A bank considers its loans and advances as non-performing assets when the borrowers became unable to pay the interest along with the principal amount on due date. Through this study the researcher aims to ascertain the management of non- performing assets in Union Bank of India. This study is based on descriptive in nature and analysed the data which are collected from secondary sources of data. Through this study the researcher has find that the level of non-performing assets has decreased which has increased the level of profitability.